Interactive effects of temperature and grazing by seagrass limpets (Siphonaria compressa and Fissurella mutabilis) on seagrass (Zostera capensis) - Waspe, Christopher Themba (Marine Research (MA-RE) Institute, 2016)
Climate change is a reality. One of the main ecological concerns regarding climate change is the predicted increase in atmospheric and sea temperatures. The latter is expected to rise by roughly 2.5°C by the end of 2050 with dramatic impacts on marine ecosystems predicted around the world. Seagrass ecosystems are a good example of vital ecosystems that are threatened by climate change and other anthropogenic factors. A decline in global seagrass cover of 29% has been estimated over the last century, and at a local level, cover of the seagrass Zostera capensis has declined by 38% over the last 50 years in Langebaan Lagoon, with associated losses of invertebrate abundance by 70% in certain areas. Two limpets, Siphonaria compressa and Fissurella mutabilis depend on Zostera capensis for their survival in Langebaan Lagoon, feeding on epiphytic diatoms, filamentous algae and bacteria growing on blades on seagrass. Siphonaria compressa occurs exclusively in beds of Zostera capensis and is currently listed as critically endangered. Increasing sea temperatures have been found to directly and indirectly affect seagrass growth and survival. Temperature changes influence epiphytic microalgal growth on seagrass blades, thereby limiting light and nutrient availability to seagrasses. Key grazers, however, can potentially limit microalgal growth on seagrasses, but this function is dependant on how they respond to temperature change. Therefore, understanding the effects of temperature on seagrasses and their grazing limpets is vital to seagrass health and ultimately their persistence in marine ecosystems. To quantify the latter, a mesocosm experiment was conducted to assess the interactive effect of temperature changes and grazing by the limpets S. compressa and F. mutabilis on the seagrass Z. capensis. One of the main outcomes of the experiment was that Increasing temperatures significantly enhanced algae biomass fouling seagrass leaves. At the same time, limpet feeding significantly decreases algal fouling, especially at higher temperatures. S. compressa was significantly more effective at removing algae from the blades of Z. capensis than F. mutabilis, particularly at higher temperatures. Increasing temperatures and the feedback from grazer presence had no substantial impact on the growth of Z. capensis but vi significantly influenced the survival of the seagrass blades. Another important result for predicting future effects of temperature rise on seagrass ecosystems was that mortality of F. mutabilis was significantly greater than S. compressa at higher temperatures. Overall, the study demonstrates that increasing temperatures clearly impacts the dynamics of seagrass ecosystems, either directly by impacting seagrasses or indirectly, by increasing algal fouling. The presence of limpets is also vital in controlling the levels of algae, with S. compressa performing more of a beneficial role in keeping blades of seagrass free of fouling. These findings are relevant for the conservation of seagrasses in Langebaan Lagoon, as they indicate the importance of preserving populations of the endangered limpet S. compressa in order to maintain healthy functioning seagrass ecosystems under future warming scenarios.